The United Kingdom’s Environmental Tax Reflection on its Economic Growth - Kamaran Abdulla, Shene Mohammad (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
A tax system is a crucial tool for achieving the government's environmental objectives, notably achieving future net-zero greenhouse gas emissions. Governments, scholars, and stakeholders have long acknowledged the potential of the tax system in this regard. This research aims to investigate the cause between environmental-related taxes and GDP in the United Kingdom by correlating various environmental tax measures with GDP, such as transportation tax, gas and diesel tax, and renewable energy concerning adjusted net savings. The annual time series data has been used from 2000 to 2020, gathered from reliable sources. The ADF unit root test, Johansson co-integration, and Granger causality tools are applied. The findings reveal some evidence of long-term causation between GDP and increasing environmental tax revenues and some causality evidence of medium-run going the other way. The ADF unit root includes the fact that the data are stationary at different levels, and the Johansson Cointegration shows the long-term correlation between environmental tax and economic growth, population has little impact on the long-term association.